KESADARAN PEREMPUAN ANGKOLA TERHADAP WARISAN DI DESA BANGAI KECAMATAN TORGAMBA KABUPATEN LABUHAN BATU SELATAN - Efendi, Rijal (Fakultas Agama Islam, 2020)
Although the distribution of inheritance has been arranged by Allah SWT, but there are still disputes between humans in terms of dividing inheritance as happened in the Muslim community in Bangai Village, Torgamba District, Labuhan Batu Selatan Regency, even though the distribution has been arranged, but disputes often occur. Field data on the distribution of inheritance of Muslim communities in Bangai Village, Torgamba District was collected through research, to find out about the distribution of inheritance to Angkola girls in Bangai Village, Torgamba District, Labuhan Batu Selatan Regency. knowledge assisted with library data relating to this reason to obtain relevant results. After it is successful, it is collected, grouped and analyzed. Based on the analysis of these data, it was found that there are a variety of laws that apply to the Muslim community in Bangai Village, Torgamba District. So that Islamic inheritance law cannot be applied purely to the Muslim community of Bangai Village. The applicable inheritance law is Angkola's customary inheritance law which is carried out by dividing the assets to only boys and not getting girls. This is certainly not in line with Islamic inheritance law.